Twin default crises - Caterina Mendicino; Kalin Nikolov; Juan Francisco Rubio-Ramírez; Javier Suárez; Dominik Supera (European Central Bank (ECB), 2020)
We study the interaction between borrowers' and banks' solvency in a quantitative macroeconomic model with financial frictions in which bank assets are a portfolio of defaultable loans. We show that ex-ante imperfect diversification of bank lending generates bank asset returns with limited upside but significant downside risk. The asymmetric distribution of these returns and their implications for the evolution of bank net worth are important for capturing the frequency and severity of twin default crises - simultaneous rises in firm and bank defaults associated with sizeable negative effects on economic activity. As a result, our model implies higher optimal capital requirements than common specifications of bank asset returns, which neglect or underestimate the impact of borrower default on bank solvency.
Keywords: G01; G28; E44; 330; Bank default; Firm default; Financial Crises; Bank Capital Requirements